The Modern Diagnostic Approach to Community-Acquired Pneumonia in Adults - Chalmers, James D. (Seminars in Respiratory and Critical Care Medicine, 2016)
Respiratory tract infections, the majority of which are community acquired, are among the leading causes of death worldwide and a leading indication for hospital admission. The burden of disease demonstrates a “U”-shaped distribution, primarily affecting young children as the immune system matures, and older adults as the process of immunosenescence and accumulation of comorbidities leads to increased susceptibility to infection. Diagnosis of community-acquired pneumonia (CAP) is traditionally based on demonstration of a new infiltrate on a chest radiograph in a patient presenting with an acute respiratory illness or sepsis. Advances in diagnosis have been slow, and although there are increasing data on the value of computed tomography or lung ultrasound as more sensitive diagnostic methodologies, they are not widely used as initial diagnostic tests. There are a wide range of differential diagnoses and pneumonia “mimics” which should be considered in patients presenting with CAP. Once the diagnosis of CAP has been made, identifying the causative microorganism is the next stage in the diagnostic process. Traditional culture-based approaches are relatively insensitive and achieve a positive diagnosis in only 30 to 70% of cases, even when rigorously applied. Urinary antigen tests, polymerase chain reaction assays, and even next-generation sequencing technologies have become available and are increasing the rates of positive diagnosis. In an era of increasing antimicrobial resistance, the accurate diagnosis of CAP and determining the causative pathogen are ever more important. Getting these both right is key in reducing both morbidity and mortality from CAP, and appropriate antimicrobial stewardship which is now an international healthcare priority.
Keywords: chest radiograph; community-acquired pneumonia; epidemiology; microbiology; polymerase chain reaction; risk factors; Streptococcus pneumoniae